Penerapan Konsep Guru Profesional Dalam Penanaman Akhlak Siswa Pada Surat Ali Imran Ayat 159: Studi Kasus MI Ibnu Aqil Pekanbaru - Salsabila Almahda; Wismanto Wismanto; Radhiyatul Fithri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Educators are one of the figures that has a major role in shaping human resources, because educators can be as teachers, guides who always guide in goodness, as well as leading students in the demand of science. To be an exemplary and professional teacher, an educator is encouraged to follow examples based on Hadits and the Quran that can help teachers to have maximum working spirit and focus on the profesionalisme that is based on the Quran. The purpose of this study is to explain how the role of teachers in applying the concept to Ali Imran letter verse 159 becomes a professional teacher in instilling the morality of students at MI Ibnu Aqil Pekanbaru. Research in this thesis uses case study research, also known as case study, which is a qualitative research method used to investigate a particular problem or object, mainly in the field of social sciences. Case research is used in sociology to evaluate a real event or situation (directly). The results of this study show how to address the phenomenon of moral degradation that occurs in children and adolescents, especially students at the level of MI, by applying the values of moral education in Al-Quran Surat Ali-Imran Ayat 159, which covers many values, for that how important the intelligence and role skills that must have professional teachers to help refresh and create a generations of moral karimah.